Macrophage‐dependent clearance of systemically administered B16BL6‐derived exosomes from the blood circulation in mice. Issue 1 (9th February 2015) - Imai, Takafumi; Takahashi, Yuki; Nishikawa, Makiya; Kato, Kana; Morishita, Masaki; Yamashita, Takuma; Matsumoto, Akihiro; Charoenviriyakul, Chonlada; Takakura, Yoshinobu
Abstract : Previous studies using B16BL6‐derived exosomes labelled with gLuc–lactadherin (gLuc‐LA), a fusion protein of Gaussia luciferase (a reporter protein) and lactadherin (an exosome‐tropic protein), showed that the exosomes quickly disappeared from the systemic circulation after intravenous injection in mice. In the present study, the mechanism of rapid clearance of intravenously injected B16BL6 exosomes was investigated. gLuc‐LA‐labelled exosomes were obtained from supernatant of B16BL6 cells after transfection with a plasmid DNA encoding gLuc‐LA. Labelling was stable when the exosomes were incubated in serum. By using B16BL6 exosomes labelled with PKH26, a lipophilic fluorescent dye, it was demonstrated that PKH26‐labelled B16BL6 exosomes were taken up by macrophages in the liver and spleen but not in the lung, while PKH26‐labelled exosomes were taken up by the endothelial cells in the lung. Subsequently, gLuc‐LA‐labelled B16BL6 exosomes were injected into macrophage‐depleted mice prepared by injection with clodronate‐containing liposomes. The clearance of the intravenously injected B16BL6 exosomes from the blood circulation was much slower in macrophage‐depleted mice than that in untreated mice. These results indicate that macrophages play important roles in the clearance of intravenously injected B16BL6 exosomes from the systemic circulation.